PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KEPATUHAN PENGUNGKAPAN TRANSAKSI PIHAK BERELASI - Grace Olivia, (2021)
This research aims to determine the effect of good corporate governance on compliance disclosure of related party transaction of listed manufacturing companies in Indonesia Stock Exchange in the period 2017 - 2019. The type of this research is quantitative research that uses secondary data based on annual report. A sample of this research consisted of 117 manufacturing companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t test). Based on the result of data analysis, it can be concluded that (1) independent commissioners does not has a significant effect on disclosure of related party transactions, (2) audit committee from independent commissioner has a significant positive effect on disclosure of related party transactions, (3) concentrated ownership does not has a significant effect on disclosure of related party transactions, (4) audit quality does not has a significant effect on disclosure of related party transactions, and the control variables, namely (6) firm size does not have a significant effect on disclosure of related party transactions